Soul and its Implication in Philosophy, Medicine and Religion - Shamima Parvin Lasker; Arif Hossain (Bangladesh Journal of Bioethics, 2021)
The reality is that soul and death are the integral part of human life. The soul is the essence of life as fuel is the energy that runs the automobile or the light that makes the eye see. We all see the human body when the soul leaves and the human body is left senseless and ultimately dissolves into the earth. Why we do not have knowledge about soul where this element is the integral part of our human life. Most of us are not aware about this and do not like to research on it even do not discuss in life time. There is hardly any study on soul. Western bioethics totally omits discussion on the soul, though they discussed on “good death”. Only religion discussed soul elaborately specially Islam. No literature is available from Bangladesh. Therefore, the present study has been done to expand the body of knowledge on soul in the light of current theory with a view to aware people for further research for understanding and comparing with concept of philosophical, religious and medical variation.